EFFECTIVENESS MODEL VOCATIONAL HIGH SCHOOL IN THE CITY OF SEMARANG (The Journal of Educational Development, 2014)
Vocational School has a unique character, its output should really be prepared to have competence in the workplace in accordance with the chosen skill. In reality based on research results In reality based on the results of research and development agency of Central Java Central Java shows the number of graduates of vocational schools and private State in Central Java between 95 % to 100 % , of the passing range are absorbed into jobs that match their expertise program is 30 % up to 50 % . This study aims to determine the effect of principal leadership , teacher competence , school climate and the school committee on the effectiveness of vocational high school in the city of Semarang. The design of this research is a quantitative research approach through a confirmatory factor analysis model. Its population is a vocational high school teachers in public and private in Semarang City with 293 respondents. The collected data were analyzed through SEM analysis using software programs VPLS (Visual Partial Least Square). Results reveal that the principal leadership, teacher competence, school climate and the school committee has a positive and significant impact on the effectiveness of vocational high school in the city of Semarang. Of the four principal leadership factors have the greatest influence with the value of load factor of 4,6899, the school committee with a value of 3,6914, with the teacher's competence value of 2,6002 and last school climate with a value of 2,2467. Based on these results, the variables principal leadership, teacher competence, school climate and the school committee can be the foundation for efforts to improve the effectiveness of vocational school, through its dimensions and indicators.